2013
DOI: 10.1136/bmjopen-2013-002715
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of schemes that refine referrals between primary and secondary care—the UK experience with glaucoma referrals: the Health Innovation & Education Cluster (HIEC) Glaucoma Pathways Project

Abstract: ObjectivesA comparison of glaucoma referral refinement schemes (GRRS) in the UK during a time period of considerable change in national policy and guidance.DesignRetrospective multisite review.SettingThe outcomes of clinical examinations by optometrists with a specialist interest in glaucoma (OSIs) were compared with optometrists with no specialist interest in glaucoma (non-OSIs). Data from Huntingdon and Nottingham assessed non-OSI findings, while Manchester and Gloucestershire reviewed OSI findings.Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 18 publications
3
47
1
Order By: Relevance
“…By combining the IOP criterion with any other JCG criterion,12 the predictive value increased substantially, and this is in agreement with previously published data 3 6 13. Thus, our findings support the statement that ‘IOP-only referrals represent a waste of hospital outpatient resource’ 13. Interestingly, family history of glaucoma had a low positive predictive value, even when it was combined with other referring criteria.…”
Section: Discussionsupporting
confidence: 89%
“…By combining the IOP criterion with any other JCG criterion,12 the predictive value increased substantially, and this is in agreement with previously published data 3 6 13. Thus, our findings support the statement that ‘IOP-only referrals represent a waste of hospital outpatient resource’ 13. Interestingly, family history of glaucoma had a low positive predictive value, even when it was combined with other referring criteria.…”
Section: Discussionsupporting
confidence: 89%
“…There are emerging models of eye care in the community that try to reduce the number of false-positive referrals to hospital eye services. [53][54][55] Their effectiveness, efficiency and acceptability need to be evaluated in primary research before implementing change. The GATE study provides robust data on how such services might be reconfigured.…”
Section: Economic Evaluation Resultsmentioning
confidence: 99%
“…Ratnarajan 2013 has recently reported on suspected glaucoma referral patterns by optometrists with or without special interest in glaucoma in the UK. They concluded that a referral for suspected glaucoma is based characteristically on nding an elevated IOP, an abnormal optic disc appearance, an abnormal visual field, or a combination of these.…”
Section: Introductionmentioning
confidence: 99%